Ambiente alimentar do consumidor no entorno dos Equipamentos Públicos de Segurança Alimentar e Nutricional de Belo Horizonte, Minas Gerais - Nayhanne Gomes Cordeiro (2021)
BACKGROUND: Food and nutritional security consists of realizing the right to permanent access to healthy and balanced food, with access dictated by socioeconomic, behavioral, cultural and environmental factors. Food choices are influenced by factors such as availability, variety, quality, price and advertising of food within establishments. To strengthen access to healthy food, Food and Nutrition Security Facilities (FNSF) was implemented. However, it is not known whether the presence of this equipment changes the availability, variety and promotion of the food offered in establishments close to FNSF. OBJECTIVE: To investigate the consumer's food environment in areas with and without FNSF. METHODS: Cross-sectional study carried out in areas with and without FNSF in Belo Horizonte-MG, Brazil. To define the investigated area, a 500m buffer was drawn around the FNSF and the centroides of the census sectors in areas without FNSF, considering a minimum distance of 1000m between them. A total of ten areas with FNSF and ten areas without FNSF were investigated. All the establishments selling food for home consumption were audited on the spot, using a validated questionnaire (DURAN, et al, 2013). Variables of availability, variety and promotion of the food that comprised the Healthy Food Store Index (HFSI) were evaluated. These attributes were described using measures of central tendency and dispersion and compared between the areas using ANOVA and Tukey test. RESULTS: The selected FNSF were sacolões ABasteCer (n = 2), street markets (n = 3); Organic food markets (n = 1), municipal markets (n = 2) and direto da roça (n = 2). Altogether 131 establishments and 17 FNSF participated, 72 (48.6%) were in areas with FNSF and 76 (51.3%) in areas without FNSF. The average access index was 7 (0-16), with the highest indexes found in the sacolões (HFSI = 13; 7-16) and FNSF (HFSI = 12; 1-16). The lowest access rates were observed in convenience store and bakery (HFSI = 1; 0-9) and local markets (HFSI = 2; 0-12). There was no significant difference in HFSI between areas with and without FNSF. The average availability and variety of fruits and vegetables (FH) was higher among FNSF, sacolões and supermarkets (p <0.001). The average availability of ultra-processed foods and their promotion was higher among convenience store and bakery, local markets and supermarkets (p <0.001). The variety of ultra-processed foods was greater in supermarkets. CONCLUSION: Sacolões and FNSF showed higher rates of access to healthy foods, due to the greater availability and variety of FH. The index of access to healthy food did not vary according to areas with and without FNSF, reflecting the low influence of EPSAN on the dynamics of commercialization.